Peran Pendidikan Nilai dalam PKn untuk Membentuk Karakter Siswa di Era Digital: The Role of Values PKn to Shape Students' Character in the Digital Era - Riska Armianti; Ndona, Yakobus; Saragi, Daulat (ITScience (Information Technology and Science), 2024)
The main problem that is a challenge in character formation through civic education is the increasing development of the digital era which changes the mindset and character of students. Therefore, value education in civics is needed to shape the character of elementary school students in the current digital era. This study uses a literature study method by searching for sources such as scientific articles, journals, and documents related to research problems. The data used are secondary data obtained from relevant books, articles, and journals. Data collection techniques include literature studies, listening techniques, and note-taking techniques. Through literature studies and empirical data analysis from several studies, it was found that the role of value education in civics has an important role in building the moral character of students in the digital era. Not only is it able to form good student character, but it also prepares students to face various challenges that arise due to negative content such as cyberbullying, hoaxes, gadget addiction, pornographic sites, and other unethical behavior. In the midst of rapid technological developments, civics aims not only to make students academically intelligent, but also to form a strong, creative, critical, and active moral character. Civic Education provides students with the skills to develop attitudes of tolerance, peace, harmony, and respect for diversity. Value education in Civic Education (PKn) plays a very important role in shaping students' character, especially in the challenging digital era. Digital technology provides broad access to information, but also has negative impacts. Therefore, a structured and innovative approach is needed in learning PKn, which not only educates students about the values ??of Pancasila, but also helps them develop digital literacy and online ethics. The role of families, teachers, and the community is also very crucial in supporting students' character education.